Some specifics problems of English foreign language leaner’s in extensive reading - MASWA KAFUNDA, Jules; NKOKO LUKU, Marcel (Éducation et développement, 2018)
Pour développer une telle compétence (capacité) linguistique, l’enseignant d’Anglais doit savoir que ses élèves n’apprennent pas seulement la lecture mais aussi une capacité ou volubilité d’expression orale de la langue tout en faisant découvrir les différences de sons, prononciation ou intonation. Il a été constaté que les apprenants de cette langue éprouvent beaucoup des lacunes pour interpréter le message d’un texte pour la lecture. Les apprenants sont incapables et bloqués devant la lecture par une incompréhension notoire du message. Ainsi, cet article traite des problèmes et remèdes intrinsèques et extrinsèques de la lecture d’Anglais en vue de relever certaines failles de message compréhensible de quelques textes d’Anglais et de renforcer la compréhension dans la lecture. Abstract The teaching of English as a second foreign language considered by most linguists must first increase the use of cursive reading. To develop such a linguistic competence (capacity), the English teacher must know that his pupils not only learn reading but also a capacity or volubility of oral expression of the language while making discover the differences of sounds, pronunciation or intonation. It has been found that learners of this language have many shortcomings in interpreting the message of a text for reading. Learners are unable and stuck in front of reading by a notorious misunderstanding of the message. Thus, this article discusses the intrinsic and extrinsic problems and remedies of reading English in order to identify certain flaws in the comprehensible message of some English texts and to enhance comprehension in reading.